Analysis of Netizens Linguistic Politeness in the Comment Section of Posts about Naturalised Players on the TikTok - Al-Hakim, Muhammad Farhan; Ritonga, Muhammad Husni (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study examines linguistic politeness strategies among netizens in the comment section of the TikTok account @erick.thohir concerning the naturalisation of football players. Employing a descriptive qualitative method, comments were categorised into criticism, questions, support, and other forms of expression. Brown and Levinson’s politeness theory was applied to identify polite and impolite strategies, while Labov’s sociolinguistic framework revealed how variations in speech styles reflect social identities. Findings show that, despite the informal and emotive tone of interaction, netizens largely uphold politeness norms in voicing opinions. Theoretically, this study contributes to digital pragmatics by integrating politeness theory and sociolinguistics to highlight nationalism-oriented discourse on a short-video platform. It demonstrates how TikTok serves as a site where digital communication ethics, identity negotiation, and civic participation intersect.